CASTE DEVELOPMENT IN HYMENOPTERA, A MOLECULAR VIEW FOR FARMING IMPROVEMENT OF STINGLESS BEES - D.M. Moreno-Cálix; F. Guillén-Chable; M.A. Gallardo Flores; K.J. Cantarero; L.C. Rodríguez-Zapata; Enrique Castano (Tropical and Subtropical Agroecosystems)
Background: The evolution and genetic elements for the development of the caste is an enigma in Hymenoptera, as well as the total impact that the genetic elements given in the food of the larvae have on the development of bees. During the last decades, micro RNAs (miRNAs) from nurse bee secretions in larval food have been found to constitute an additional element in the regulatory control of caste determination. Furthermore, social differentiation is a complex developmental process influenced by genetic, epigenetic, and environmental factors. Objective: To examine and summarize miRNAs as a regulatory component of larval food with an effect on caste development in eusocial hymenoptera. Methodology. The sequences of miRNAs expressed in eusocial bees were obtained from miRBase.org. MUSCLE V.3 enabled alignment and correction was carried out using Fast.Dist. The TreeDyn software was used to obtain the phylogenetic trees. Results: The role of diet and the relationship with microRNAs in caste differentiation and regulation may be part of a general mechanism that involves selective plant genetic information necessary for insect development. Implications: The in vitro cultivation of stingless bees is a practice that is already carried out in some species of commercial importance; However, studies that demonstrate how development, differentiation and regulation of gene expression would be shaping the differentiation of different castes are still gaps that must begin to be addressed. In vitro breeding would require the study of environmental and molecular variables that would modulate the expression of the castes. Conclusion: The biogenesis, regulation and functions of microRNA in Eukarya are still obscure, however, some light has been shed on the molecular basis of caste differentiation in eusocial bees modulated by 2 miRN transfer pathways; endogenous and exogenous.